The Relationship Between Pregnant Women's Adherence to Taking Iron (Fe) Tablets and the Incidence of Anemia - Dormina Dormina; novida nengsih; Masrina Naomi Wulantari Simanjuntak (STIKES Garuda Putih, 2026)
Background: Anemia among pregnant women is a significant health problem that increases the risk of pregnancy and childbirth complications. One of the main strategies to prevent anemia is the regular consumption of iron (Fe) tablets during pregnancy. Pregnant women's adherence to taking iron tablets is an important factor in reducing the incidence of anemia. Objective: This study aimed to determine the relationship between pregnant women's adherence to iron (Fe) tablet consumption and the incidence of anemia in the working area of the Kenali Besar Public Health Center, Jambi City. Methods: This study aims to determine the relationship between pregnant women's adherence to taking iron (Fe) tablets and the incidence of anemia in the working area of ​​the Kenali Besar Community Health Center, Jambi City. Results: The majority of pregnant women were non-adherent to iron (Fe) tablet consumption, accounting for 40 respondents (72.7%). Most respondents were found to have anemia, with 36 respondents (65.5%). Statistical analysis showed a significant relationship between pregnant women's adherence to iron (Fe) tablet consumption and the incidence of anemia in the working area of the Kenali Besar Public Health Center, Jambi City (p-value = 0.000; p < 0.05). Conclusion: Higher adherence to iron (Fe) tablet consumption among pregnant women is associated with a lower risk of anemia. Health professionals are encouraged to continuously improve education and motivation for pregnant women regarding the importance of regularly taking iron (Fe) tablets to prevent anemia. Keywords: Adherence, Iron (Fe) Tablets, Anemia, Pregnant Women